Beast Boy: Teen Titans #2 - Garcia, Kami; Picolo, Gabriel; Haynes, Rob; Downie, Gabriela (Burbank, CA : DC Ink, 2020)
Seventeen-year-old Garfield Logan finally impresses the social elite at his high school, but popularity comes at a price when he undergoes sudden physical changes as the dares from his new friends escalate.
"Beast Boy created by Arnold Drake."
Ages 13-17.
Keywords: Schools -- Fiction; Popularity -- Fiction; High schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Graphic novels